Analisis Penentuan Frekuensi Pengiriman Guna Meminimalkan Biaya Transportasi Dengan Menggunakan Metode Distribution Requirement Planning (DRP) - Fauzi, Rachmad Rizky; Puspanantasari, Erni (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
PT. SM, a company engaged in fertilizer production. The purpose of the study is to identify and address the problems facing companies with less optimal shipping frequency and high transportation costs. In this study, DRP techniques were selected because they allowed the planning and scheduling of product distribution to be efficient. The research process begins with data collection such as product demand, operational cost, and shipping routes. Analysis is conducted to identify more effective sales management solutions. The results of the survey showed that the DRP method reduced sales costs significantly compared to the methods the company previously used. Based on calculation, the total distribution cost of the company incurred before applying the DRP method in a given delivery period is Rp 22.050.000. After applying the DRP methode, the total distribution cost reaches Rp 14. 700. 000,- equivalent to savings of Rp 7. 350. 000 or about 33.33%. Thus, the implementation of DRP methods not only reduces transportation costs but also improves the efficiency of product distribution management.. Keywords : Cost Analysis, DRP, EOQ, Forecasting